POOR ACADEMIC SUPERVISION AUTHORITY OF THE HEAD OF MADRASAH ALIYAH(MA) IN IMPROVING TEACHER PERFORMANCE - Herman, Herman; Jamin, Hanifuddin; Hasnadi, Hasnadi (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
Abstract: The head of the madrassa in carrying out the main duties and functions of academic supervision has optimal authority in improving teacher performance. This study aims to analyze the use of the academic supervisory authority of the madrassa principals in improving the performance of Madrassa Aliyah (MA) teacher in West Aceh District. This study uses a descriptive analytical approach in revealing the problem of using the authorities, obligations and powers of the madrassa principals in improving teacher performance. Methods of data collection were carried out through observation, interviews and study of program documents and academic supervision activities. Data processing techniques were conducted by means of data verification, data presentation, data reduction, and drawing conclusions from research results. The data analysis technique is by reflecting, interpreting and compiling an action plan on the research results. The results showed that the use of the academic supervision authority of the madrassa principals was still categorized as weak in improving teacher performance. Madrasah principals still do not take it seriously in using their authority in planning academic supervision programs. The heads of the madrassas in carrying out the obligations of implementing the academic supervision program are still not in accordance with the applicable technical instructions. The power of the heads of madrassas in carrying out innovations in academic supervision programs has not been utilized properly to improve teacher performance. These findings can be recommended to the head of the Regency/City Ministry of Religious Affairs Office and madrasa supervisors to carry out programmatic guidance and training for madrasa principals on the implementation of academic supervision in Madrassa. Keywords: Weak Authority; Academic Supervision of the Head of Madrassa; Teacher Performance